2007
DOI: 10.1083/jcb.200702026
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for the nuclear membrane protein emerin in association of the centrosome to the outer nuclear membrane

Abstract: The type II inner nuclear membrane protein emerin is a component of the LINC complex that connects the nuclear lamina to the actin cytoskeleton. In emerin-null or -deficient human dermal fibroblasts we find that the centrosome is detached from the nucleus. Moreover, following siRNA knockdown of emerin in wild-type fibroblasts, the centrosome also becomes detached from the nucleus. We show that emerin interacts with tubulin, and that nocadozole-treated wild-type cells phenocopy the detached centrosome character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
169
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(186 citation statements)
references
References 29 publications
14
169
0
Order By: Relevance
“…Indeed, values of 40-50 m are not unusual. To put these numbers in perspective, loss of emerin or A-type lamins leads to a 3-to 4-m separation between the centrosome and nucleus (37,38). Our findings suggest that Nesp4 expression does not simply disrupt centrosome tethering, but actively drives the separation of these structures.…”
Section: Resultsmentioning
confidence: 91%
“…Indeed, values of 40-50 m are not unusual. To put these numbers in perspective, loss of emerin or A-type lamins leads to a 3-to 4-m separation between the centrosome and nucleus (37,38). Our findings suggest that Nesp4 expression does not simply disrupt centrosome tethering, but actively drives the separation of these structures.…”
Section: Resultsmentioning
confidence: 91%
“…(31,32) In human dermal fibroblasts, it is shown that emerin and microtubules both are necessary for the association of the centrosome with the nuclear envelope. (33) From our results, we inferred the mechanism by which this interaction connects the centrosome and nucleus. We accordingly propose a model in which the centrosome is localized close to the nuclear membrane via the BRCA2-plectin interaction (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The nuclear envelope (NE) consists of the outer and inner nuclear membranes (ONM & INM) (the former being continuous with the rough endoplasmic reticulum, ER), the nuclear pore complexes (NPCs) and the nuclear lamina (NL), which together bridge the cytoskeleton and the various cytosolic organelles in the cytoplasm with the chromatin, the nuclear bodies and the nucleoskeleton inside the nucleus (Salpingidou et al 2007) (see Fig. 2).…”
Section: The Nuclear Lamina As a Stress-resistant Filamentous Networkmentioning
confidence: 99%